Continuous Flow Chlorination of Alkenyl Iodides Promoted by Copper Tubing - Nitelet, Antoine; Kairouz, Vanessa; Lebel, Hélène; Charette, André B.; Evano, Gwilherm (Synthesis, 2019)
A simple continuous flow synthesis of alkenyl chlorides from the corresponding readily available alkenyl iodides in copper reactor tubing is described. A variety of alkenyl chlorides were obtained in good to excellent yields with full retention of the double bond geometry. The reaction time was reduced by a factor of 24–48 compared to the batch process.
Keywords: copper catalysis; heterogeneous catalysis; halogen exchange; Finkelstein reaction; continuous flow process